Comparison of Ramosetron with Palonosetron for Prevention of Postoperative Nausea and Vomiting in Patients Receiving Opioid-Based Intravenous Patient-Controlled Analgesia after Gynecological Laparoscopy. (5th March 2017) - Ahn, Eun Jin; Choi, Geun Joo; Kang, Hyun; Baek, Chong Wha; Jung, Yong Hun; Woo, Young Cheol
Abstract : We aimed to compare the effects of ramosetron and palonosetron in the prevention of postoperative nausea and vomiting (PONV) in patients that received opioid-based intravenous patient-controlled analgesia (IV-PCA) after gynecological laparoscopy. We reviewed the electronic medical records of 755 adults. Patients were classified into two groups, ramosetron (group R, n = 589 ) versus palonosetron (group P, n = 166 ). Based on their confounding factors, 152 subjects in each group were selected after the implementation of propensity score matching. The overall incidence of PONV at postoperative day (POD) 0 was lower in group R compared to group P (26.9% versus 36.8%; P = 0.043 ). The severity of nausea was lower in group R than in group P on postoperative day (POD) 0 (P = 0.012 ). Also, the complete responder proportion of patients was significantly higher in group R compared to that in group P on POD 0 (P = 0.043 ). In conclusion, ramosetron showed a greater efficacy in the prevention of postoperative nausea at POD 0 compared to palonosetron in patients after gynecological laparoscopy.